2018
DOI: 10.1002/jcb.27251
|View full text |Cite
|
Sign up to set email alerts
|

Role of microRNA‐410 in molecular oncology: A double edged sword

Abstract: MicroRNAs (miRNAs) are short non-coding single-stranded RNAs, which play significant roles in the regulation of a myriad of biological processes. Overwhelmingly increasing high-impact research has also deepened our understanding about the central role of miRNAs in cancer development, metastatic spread, and development of resistance against various drugs. Recent studies have identified miRNAs that regulate RNA expression/processing and posttranscriptional expression of important oncogenes and tumor suppressors.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 27 publications
0
24
0
Order By: Relevance
“…There is an increasing evidence that the role of miR-410-3p in molecular oncology is tissue-and context-dependent. miR-410-3p may act as both oncomiR or tumor suppressor miR in different types of cancer [17]. It regulates crucial cellular processes including cell cycle, apoptosis, migration, and invasion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is an increasing evidence that the role of miR-410-3p in molecular oncology is tissue-and context-dependent. miR-410-3p may act as both oncomiR or tumor suppressor miR in different types of cancer [17]. It regulates crucial cellular processes including cell cycle, apoptosis, migration, and invasion.…”
Section: Discussionmentioning
confidence: 99%
“…However, its function seems to be reversed in some other neoplasms, where it functions as an oncomiR (non-small cell lung, liver, and colorectal cancers). It promotes or inhibits cell proliferation, invasion, migration, and apoptosis [17].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, exosomal miR-25-3p from CRC cells promotes CRC progression by inducing the formation of a pre-metastatic niche, and it may be applied as a biomarker in diagnosis, prevention of cancer metastasis [41]. Aberrant miR-410 expression has been observed in diverse types of cancers, thus playing different roles in cancer progression [42,43]. For example, Qi et al demonstrated miR-410 accelerated the proliferation and colony formation of lymphoblastic leukemia (ALL) cells through FKBP5 and Akt pathway [44].…”
Section: Discussionmentioning
confidence: 99%
“…In our previous study, we found that miR-410-3p have a lineage-specific role in pituitary adenomas and controls crucial signalling pathways and modulates tumor cells invasiveness and proliferation [20]. miR-410-3p negatively modulates CETN3, BAK1, and BRD7 to stimulate oncogenesis and positively regulates AGTR1, c-MET and SNAIL leading to the suppressed cancer progression [19]. miR-410-3p influence chemosensitivity to gemcitabine in the treatment of pancreatic ductal adenocarcinoma by inhibiting HMGB1-mediated autophagy and thus may serve as a biomarker of chemoresistance [21].…”
Section: Introductionmentioning
confidence: 98%
“…Recent studies demonstrated its role in numerous diseases including cardiomyopathy [17] and stroke [18]. It was described to play a significant role in the pathogenesis of different types of cancer as tumor suppressor miR (gastric, pancreatic, endometrial, breast and bone cancers) or oncomiR (liver, colorectal and nonsmall cell lung cancers) [19,20]. miR-410-3p can promote or inhibit cell proliferation, invasion, migration and apoptosis through different factors.…”
Section: Introductionmentioning
confidence: 99%